2015
DOI: 10.3109/09638237.2015.1078881
|View full text |Cite
|
Sign up to set email alerts
|

Migration and young people’s mental health in Canada: A scoping review

Abstract: Findings support the need to account for the array of influences on young people's mental health in relation to migration and to augment initiatives beyond the level of individual intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Most of the research with immigrant young people has tended to concentrate on familial or cultural values, intergenerational conflicts, and acculturation ( Salehi, 2010 ). In general, there has been an emphasis on individual and family-level factors and less attention to social structures and relations ( Hilario, Oliffe, Wong, Browne, & Johnson, 2015 ). The reliance on cultural and behavioral frameworks, in which culture is narrowly defined and individual health behaviors are the primary unit of analysis, has led to studies that “revert back to an apolitical and ahistorical understanding of differences between populations that eschews social inequalities and social determinants of health” ( Castañeda et al, 2015 , p. 380).…”
Section: Framework For Immigrant and Refugee Healthmentioning
confidence: 99%
“…Most of the research with immigrant young people has tended to concentrate on familial or cultural values, intergenerational conflicts, and acculturation ( Salehi, 2010 ). In general, there has been an emphasis on individual and family-level factors and less attention to social structures and relations ( Hilario, Oliffe, Wong, Browne, & Johnson, 2015 ). The reliance on cultural and behavioral frameworks, in which culture is narrowly defined and individual health behaviors are the primary unit of analysis, has led to studies that “revert back to an apolitical and ahistorical understanding of differences between populations that eschews social inequalities and social determinants of health” ( Castañeda et al, 2015 , p. 380).…”
Section: Framework For Immigrant and Refugee Healthmentioning
confidence: 99%
“…Youth (Hilario et al . ), women (O'Mahony ), and the elderly (Guruge et al . ) are particularly vulnerable subgroups within these categories.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs throughout the lifespan and is globally the second leading cause of death among 15 -29 year olds (5). In particular, the mental health of the offspring of immigrants and those in international marriages is a major public health concern (10)(11)(12). Several studies have shown that adolescents in multicultural families are likely to have poorer psychological well-being than those with monocultural backgrounds, such as lower self-esteem, marked life dissatisfaction, depression, and anxiety (2,13,14).…”
Section: Discussionmentioning
confidence: 99%